Mechanism of Repetitive Transcranial Magnetic Stimulation for Depression - PENG, Zhengwu (Shanghai Arch Psychiatry, 2018)
Depressive disorder is one of the most common mental health problems currently. However, the mechanism-based treatments for this disorder remain elusive. Repetitive transcranial magnetic stimulation (rTMS), a non-invasive procedure that could stimulate electrical activity by a pulsed magnetic field in the brain, is considered to be an effective treatment for depression. Here, we review the main findings from both clinical and basic research on rTMS for depression, including its antidepressant efficacy, basic principles, as well as its ability to regulate neural circuits, neurotransmitters and brain networks, neurogenesis in hippocampus, and synaptic, and molecular pathways.